Physiological and Biomechanical Responses to Cross-Country Skiing in Varying Terrain: Low- vs. High-Intensity - Seeberg, Trine M.; Kocbach, Jan; Danielsen, Jørgen; Noordhof, Dionne A.; Skovereng, Knut; Meyer, Frédéric; Sandbakk, Øyvind (Frontiers in Physiology, 2021)
The purposes of our study were to investigate the physiological and biomechanical responses to low-intensity (LI) and high-intensity (HI) roller ski skating on varying terrain and compare these responses between training intensities. Nine elite male skiers performed treadmill roller skiing consisting of two 21-min sessions (7x3-min laps) performed at LI and HI with the same set inclines and intensity-dependent speeds (LI/HI:distance: 5.8/7.5 km, average speed: 16.7/21.3 km/h). Physiological and biomechanical variables were measured continuously, and each movement cycle and sub-technique employed was detected and classified with a machine learning model. Both the LI and HI sessions induced large terrain-dependent fluctuations (relative to the maximal levels) in heart rate (HR, 17.7% vs 12.2%-points), oxygen uptake (V ̇O_2, 33.0% vs 31.7%-points), and muscle oxygen saturation in the triceps brachii (23.9% vs 33.4%-points) and vastus lateralis (12.6% vs 24.3%-points). A sub-technique dependency in relative power contribution from poles and skis exhibited a time-dependent shift from lap 1 to lap 7 toward gradually more ski power (6.6% vs 7.8%-points, both p<.01). The terrain-dependent fluctuations did not differ between LI and HI for V ̇O_2 (p=.50), whereas HR fluctuated less (p<.01) and displayed a time-dependent increase from lap 2 to lap 7 (7.8%-points, p>.01) during HI. Oxygen saturation shifted 2.4%-points more for legs than arms from LI to HI (p>.05), and regarding sub-technique, 14.7%-points more G3 on behalf of G2 was employed on the steepest uphill during HI (p<.05). Within all sub-techniques, cycle length increased 2–3 times more than cycle rate from LI to HI in the same terrains, while the corresponding poling time decreased more than ski contact time (all p>.05). In sum, both LI and HI XC skiing on varying terrain induce large terrain-dependent physiological and biomechanical fluctuations, similar to the patterns found during cross-country skiing competitions. The primary differences between training intensities were the time-dependent increase in HR, reduced relative oxygen saturation in the legs compared to the arms, and greater use of G3 on steep uphill terrain during HI training, whereas sub-technique selection, cycle rate, and pole versus ski power distribution were similar across intensities on flat and moderately uphill terrain.